Gendered Construction of Religious Authority in Islamic Education Textbooks under Indonesia’s Merdeka Curriculum: A Critical Discourse Analysis - Muhamad Abdul Anam; Khairil Anwar; Mowafg Abrahem Masuwd (MASI Mandiri Edukasi, 2026)
This study examines gender bias in elementary school Islamic Religious Education (IRE) textbooks under Indonesia’s Merdeka Curriculum. Although gender representation in textbooks has been widely studied, research integrating Critical Discourse Analysis with Islamic feminist perspectives in the context of religious education remains limited. This study aims to identify forms of gender bias, analyze the discursive strategies that reproduce them, and interpret their implications for the construction of religious authority. The research employed qualitative document analysis using Critical Discourse Analysis (CDA). Data were collected from 214 textual units and 96 visual illustrations in elementary-level IRE textbooks, complemented by semi-structured interviews with four Islamic education teachers in Pulang Pisau Regency, Central Kalimantan. The analysis focused on actor representation, distribution of social roles, grammatical structures, and the construction of religious leadership. The findings reveal a significant gender imbalance. Men appear as 61.7% of the main subjects and dominate 78.8% of religious leadership roles. Male characters are more frequently associated with active grammatical structures (68.2%), while women appear more often in passive constructions and domestic activities (67.8%). These patterns contribute to what this study conceptualizes as the masculinization of religious authority, where religious leadership and moral authority are discursively associated with male figures. Teacher interviews indicate awareness of this imbalance, although textbooks still strongly influence students’ perceptions of gender roles. The findings highlight the need for gender-responsive revisions of religious education materials to promote more inclusive representations.